Linguistic Relativity al-Qurâ€™Än - Ghozali, Mahbub (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
Al-Qurâ€™an is the text that contains iâ€™jÄz. However, there are disagreements about iâ€™jÄz criteria. Some people think that iâ€™jÄz is outside the text, while others assume iâ€™jÄz is in the Qurâ€™an itself. One of the scholars who agreed that iâ€™jÄz al-Qur'an is in the text of the Qurâ€™an is Abd al-QÄhir al-JurjÄnÄ«. However, al-JurjÄnÄ«â€™s explanation explaining this problem is still widely misunderstood and sometimes directs understanding of the irrational aspects. This study aims to find the reasoning iâ€™jÄz al-Qurâ€™an according to al-JurjÄnÄ« by using the linguistic relativity approach. This study found that the problem of iâ€™jÄz al-Qurâ€™an according to al-JurjÄnÄ« lies in the aspect of the language structure (al-naáº“m) which covers the whole concept contained in the language convention. With the form of iâ€™jÄz in the form of this language allows the inability of other people to make the same thing that becomes the sign iâ€™jÄz can be explained through the concept of language relativity. Therefore, al-Qurâ€™an as when Allah made it has a special reality that excels every human language.